The effect of transformational leadership and organizational culture on employee performance with job satisfaction as an intervening variable (Asian Journal of Economics and Business Management, 2023)
The aim of this research is to analyze the effect of transformational leadership and organizational culture and job satisfaction as an intervening variable on the performance of employees in the District-3 PT. Wirakarya Sakti. The sample used as a research object totaling 95 employees, while data collected using a questionnaire and then analyzed by Structural Equation Modeling (SEM) based components partial least squares path modeling (PLS-SEM). Results of the analysis showed that transformational leadership has no significant effect on employee performance, organizational culture does not significantly influence employee performance, transformational leadership has no significant effect on job satisfaction, organizational culture positive and significant impact on job satisfaction, job satisfaction has not significantly influence employee performance, and transformational leadership and organizational culture does not significantly influence employee performance mediated job satisfaction. The results of the study have implications on the determination and improvement strategy model of leadership and organizational culture to be more optimal in providing job satisfaction and improve employee performance. It is advisable in future studies to be able to add other variables that are considered influential on employee performance such as, commitment, motivation, and so forth.